An anti-doping perspective on nicotine detection in the peri-exercise period in a cohort of trained male cyclists - Mündel, T. (Current Research in Physiology, 2021)
The purpose of the present study was to investigate the detection of nicotine in athletes: before vs. after 90 min exercise, and in serum vs. urine. Serum [cotinine] was not different before vs. after exercise (31±14 vs. 29 ± 14 ng/mL, P = 0.43), although urine [cotinine] measured greater than serum (148 ± 142 vs. 31 ± 14 ng/mL, P < 0.01). Urinary [nicotine] measured greater than [cotinine] (790 ± 1176 vs. 148 ± 128 ng/mL, P = 0.05), which significantly correlated (r = 0.57, P = 0.04). These results indicate that urine [cotinine] concentration is the optimal biomarker to detect nicotine use in athletes.